Formation of Highly Ordered Nanochannel Nb Oxide by Self-Organizing Anodization - Lee, Kiyoung; Yang, Yang; Yang, Mingjun; Schmuki, Patrik (Chemistry - A European Journal, 2012)
A highly aligned nanochannel Nb oxide structure can be formed by self organizing anodization of Nb in a K2HPO4-containing glycerol electrolyte at elevated temperatures (180 °C). Under optimized electrochemical conditions, a high degree of ordering can be achieved. These layers can be used as supercapacitors.
EAM Import::2019-03-14

Increased photocurrent response in Nb-doped TiO2 nanotubes - Yang, Mingjun; Jha, Himendra; Liu, Ning; Schmuki, Patrik (Journal of Materials Chemistry, 2011)
Nb-doped TiO2 nanotube (NT) layers were grown by electrochemical anodization of Ti–Nb alloys. To successfully activate Nb doping the oxide tubes need to be annealed at sufficiently high temperatures (650 °C). For tubes doped with 0.1 wt% Nb not only a considerable increase in the electrical conductivity but also a significantly enhanced photocurrent (superior to any pure TiO2 nanotube layer (anatase or rutile)) was obtained.
EAM Import::2019-03-13

Mechanical Properties of Interfaces between Mg and SiC: An Ab Initio Study - Yao, Zhipeng; Nasiri, Samaneh; Yang, Mingjun; Zaiser, Michael (Metals, 2024)
Covalently bonded particles may exhibit extremely high strength, but their performance in the reinforcement of metal alloys crucially depends on the properties of their interfaces with the embedding matrix. Here, density functional theory is used for investigating a range of interface configurations between magnesium and silicon carbide in view of their mechanical properties. Interfaces are analyzed not only in terms of interface energy/work of separation but also in terms of the interfacial shear stresses required to induce interface-parallel displacements. These properties are studied for bilayer systems with different orientations of the Mg and SiC layers and for different terminations of the SiC layer (Si or C atoms located at the interface). The results are discussed in terms of their implication for mechanical behavior of SiC reinforced Mg alloys.
Created from Fastlane, Scopus look-up
Keywords: ab initio simulation; interface properties; magnesium; particle-reinforced composites; silicon carbide

Nb doping of TiO2 nanotubes for an enhanced efficiency of dye-sensitized solar cells - Yang, Mingjun; Kim, Dam-Hee; Jha, Himendra; Lee, Kiyoung; Paul, Jonathan; Schmuki, Patrik (Chemical Communications, 2011)
Nb-doped TiO2 nanotube (with CNb < 1 wt%) layers were successfully fabricated by self-ordered electrochemical anodization of Ti–Nb alloys. When used in dye-sensitized solar cells the efficiency enhanced by up to 30% compared to non-doped TiO2 nanotubes. IMVS measurements indicate the beneficial effect to be due to lower recombination losses.
EAM Import::2019-03-12

Self-organized TiO2 nanotubes: Visible light activation by Ni oxide nanoparticle decoration - Shrestha, Nabeen Kumar; Yang, Mingjun; Nah, Yoon-Chae; Paramasivam, Indhumati; Schmuki, Patrik (Electrochemistry Communications, 2010)
Self-organized TiO_2 nanotubes grown by anodization of Ti-substrate in a fluoride based electrolyte were loaded with Ni oxide nanoparticles by a simple chemical bath precipitation technique. The photoelectrochemical and photocatalytic activities of these nanoparticle decorated nanotubes were investigated. In comparison with the classical approaches to enhance the visible light response of TiO_2 nanotubes (N-doping), the Ni oxide loaded nanotube layers show clearly a higher visible light photoresponse and photocatalytic activity.
EAM Import::2019-03-13

Some critical factors for photocatalysis on self-organized TiO2 nanotubes - Liu, Ning; Paramasivam, Indhumati; Yang, Mingjun; Schmuki, Patrik (Journal of Solid State Electrochemistry, 2012)
In the present work, different intrinsic and extrinsic parameters are investigated that affect the photocatalytic activity of self-organized TiO2 nanotube layers. Particularly, the influence of annealing temperature and annealing atmosphere, the influence of different gas purging in the electrolyte, and the effect of applied voltage on the photocatalytic degradation rates of acid orange (AO7) are discussed. We find that the effect of the reducing gas atmosphere dominates over the anatase/rutile ratio in activating the nanotube layers. Moreover, we show that the effect of different gas purging (Ar and O2) of the electrolyte affects the reaction rate twofold: (1) by providing electron acceptor states and also by (2) a different change in the red–ox potential, i.e., the band bending in TiO2. By an external anodic voltage, the reaction rates can be increased drastically due to increased band bending. Nevertheless, the magnitude of the effect is also affected by the presence or absence of O2 in the electrolyte.
EAM Import::2019-03-13

Transition of TiO2 nanotubes to nanopores for electrolytes with very low water contents - Wei, Wei; Hauser, Christina; Wei, Wei; Berger, Steffen; Hauser, Christina; Meyer, Karsten; Yang, Mingjun; Schmuki, Patrik (Electrochemistry Communications, 2010)
Over the past decade, the electrochemical formation of self-organized nanotube layers in dilute fluoride containing electrolytes has been studied intensively. In the present work, we show that by anodization of Ti in similar electrolytes but containing only very low water contents, the formation of ordered TiO nanoporous structures can be observed. I.e., the water content in the electrolyte is the critical factor that decides whether self-ordered oxide tubes or pores are formed. This supports the concept that tube formation originates from ordered porous oxide by a "pore-wall- splitting" mechanism. © 2010 Elsevier B.V. All rights reserved.

Visible-light-induced photocatalysis using self-organized TiO 2 nanotubes decorated with AgBr deposits - Shrestha, Nabeen Kumar; Yang, Mingjun; Paramasivam, Indhumati; Schmuki, Patrik (Semiconductor Science and Technology, 2011)
Self-organized TiO2 nanotubes formed anodically in fluoride ion containing electrolyte were loaded with AgBr clusters from a precipitation reaction bath. The photoactivities of these nanotubes for decomposition of an azo dye were investigated under visible light irradiation and compared with those of the N-doped self-organized TiO2 nanotubes and neat TiO2 nanotubes. Compared with the N-doped nanotubes, the AgBr-loaded nanotubes demonstrate a significantly higher visible-light-driven photocatalytic activity—even higher than for neat nanotubes irradiated with UV light.
EAM Import::2019-03-12